PERSONALITY DISORDERAS SEEN IN THE JOKER MOVIE BY TODD PHILLIP - Abdur Rahman; Ulfatmi Azlan; Firdiansyah Firdiansyah (Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2020)
This research discusses personality disorder as seen in main character in the movie Joker. Personality disorder can be recognized in adolescence because the structure of disfunctional characteristics at that stage is similar to the structure of personality disorder in adulthood (Westen et al. 2003). Biological and psychological considerations, personality disorder develop in a socio structural context and appear to be socially sensitive. Through this movie, it can be concluded that there are five kinds of personality disorder reflected to the Joker as the main character in Joker movie by Todd phillips, they are borderline personality disorder, depressive personality disorder, sadistic personality disorder, antisocial personality disorder, and negativistic personality disorder. There are two causes of personality disorder that influence Joker as the main character they are psychological factors and environmental factors.